Me and white supremacy [compact disc, unabridged] : combat racism, change the world, and become a good ancestor - Saad, Layla F (Blackstone Publishing, 2020)
"Layla F. Saad teaches listeners how to dismantle the privilege within themselves so that they can stop (often unconsciously) inflicting damage on people of color, and in turn, help other white people do better, too."--Page [4] of cover.